Bronchiectasis: how to be an orphan with many parents?. Issue 1 (January 2016) - Goeminne, Pieter C.; De Soyza, Anthony
When René Laennec first described bronchiectatic lesions, he wrote: " Je me contenterai donc de donner deux exemples propres à faire connaître plus amplement l'altération organique assez rare dont il s'agit " [1]. Loosely translated, it shows us that during his discovery he had the conviction that bronchiectatic lesions were a rather rare phenomenon. However, at that time, Laennec was the first and only person to characterise these lesions, suggesting that his contemporaries had completely overlooked their existence. What is unsought will go undetected. Bronchiectasis, an orphan disease in the spotlight: more common than previously thought yet lots still to discover http://ow.ly/Ut1eT